PREVALENCE OF CHRONIC KIDNEY DISEASE IN OBSTRUCTIVE UROPATHY SECONDARY TO UROLITHIASIS - Anwar Shahzad; Sumera Kazmi; Raja Asim Shafique; Muhamad Usman Zia; Kafeel Azhar; Sofia Shoukat (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Recent population research has indicated that individuals with symptomatic kidney stones are at a heightened risk for chronic kidney disease (CKD). While kidney stones are not typically recognized as the primary cause of end-stage renal disease (ESRD), they may still play a significant role as contributing factors. Interestingly, CKD can offer some protection against the formation of kidney stones due to a marked decrease in urinary calcium excretion. Among those who form stones, individuals with rare genetic disorders (such as cystinuria, primary hyperoxaluria, Dent disease, and 2,8 dihydroxyadenine stones), recurrent urinary tract infections, struvite stones, hypertension, and diabetes appear to be at the greatest risk for developing CKD. The primary pathway through which kidney stones lead to CKD is generally linked to obstructive uropathy or pyelonephritis; however, crystal plugs in the ducts of Bellini and parenchymal damage resulting from shockwave lithotripsy may also play a role. The historical transition towards less invasive surgical techniques for managing kidney stones has likely positively influenced the risk of CKD. In potential kidney donors, a history of symptomatic kidney stones, but not those identified through radiographic imaging on computed tomography scans, was correlated with albuminuria. Additionally, kidney stones identified via ultrasound screening have been linked to CKD within the broader population. There is a need for further research that more accurately classifies CKD, better characterizes stone formers, thoroughly addresses potential confounding factors related to comorbidities, and employs active follow-up methods to mitigate detection bias.